The metabolic reprogramming and vulnerability of SF3B1 mutations. (3rd May 2020) - Dalton, W. Brian
ABSTRACT: Mutations in the splicing factor 3b subunit 1 ( SF3B1 ) gene create a neomorphic protein that disrupts RNA splicing, but the downstream consequences of this missplicing are unclear. Our recent study of isogenic human cells demonstrated that SF3B1 MUT induces reprogramming of energy metabolism and a targetable vulnerability to deprivation of the nonessential amino acid serine.